2020
DOI: 10.1038/s41416-020-01198-5
|View full text |Cite
|
Sign up to set email alerts
|

Fusobacterium nucleatum confers chemoresistance by modulating autophagy in oesophageal squamous cell carcinoma

Abstract: Background Fusobacterium nucleatum (F. nucleatum) is a gut microbe implicated in gastrointestinal tumorigenesis. Predicting the chemotherapeutic response is critical to developing personalised therapeutic strategies for oesophageal cancer patients. The present study investigated the relationship between F. nucleatum and chemotherapeutic resistance in oesophageal squamous cell carcinoma (ESCC). Methods We examined the relationship between F. nucleat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 45 publications
0
55
0
Order By: Relevance
“…The presence of P. gingivalis in ESCC patients has also been correlated with ESCC stage, poor prognosis, and reduced chemotherapy efficacy [ 170 , 171 , 172 ]. Similarly, F. nucleatum DNA was found to be present at higher levels in ESCC cancer tissues than in paired adjacent nontumor tissues as measured by qPCR [ 173 ], and high levels of F. nucleatum in ESCC tumor tissues have been correlated with a poor prognosis and lower chemotherapeutic response [ 174 , 175 ]. These studies suggest that specific bacteria such as P. gingivalis and F. nucleatum may potentially be useful as prognostic markers, but this does not necessarily indicate that these bacteria play prominent roles in the etiology of ESCC.…”
Section: Esophageal Microbiome and Ecmentioning
confidence: 99%
“…The presence of P. gingivalis in ESCC patients has also been correlated with ESCC stage, poor prognosis, and reduced chemotherapy efficacy [ 170 , 171 , 172 ]. Similarly, F. nucleatum DNA was found to be present at higher levels in ESCC cancer tissues than in paired adjacent nontumor tissues as measured by qPCR [ 173 ], and high levels of F. nucleatum in ESCC tumor tissues have been correlated with a poor prognosis and lower chemotherapeutic response [ 174 , 175 ]. These studies suggest that specific bacteria such as P. gingivalis and F. nucleatum may potentially be useful as prognostic markers, but this does not necessarily indicate that these bacteria play prominent roles in the etiology of ESCC.…”
Section: Esophageal Microbiome and Ecmentioning
confidence: 99%
“…Fang JY from Shanghai Institute of Digestive Diseases pointed out that F. nucleatum can promote resistance to chemotherapeutic drugs in CRC patients by affecting autophagy-regulating miRNAs [ 36 ]. For other cancers, studies have shown that F. nucleatum regulates the expression of endogenous LC3 and ATG7 and the formation of autophagosomes, resulting in chemoresistance to 5-FU, cisplatin (CDDP), and docetaxel [ 115 ].…”
Section: Crosstalk Between Microbiota and Autophagy In Cancer Developmentmentioning
confidence: 99%
“…A study from 2020 by Liu Y et al assessed the relationship between chemotherapeutic resistance in esophageal squamous cell carcinoma (ESCC) and Fusobacterium nucleatum . Results showed that ESCC patients which had Fusobacterium nucleatum infection presented lesser therapeutic response to chemotherapy, mostly to 5-fluorouracil, cisplatin and docetaxel, due to the modulation of autophagosome formation induced by Fusobacterium nucleatum [ 83 ].…”
Section: The Impact Of Long-term Antibiotherapy On the Intestinal Microbiome In Crc Patientsmentioning
confidence: 99%